A DFT rationalization of the room temperature photoluminescence of Li2TiSiO5 - Orhan, E.; Albarici, V. C.; Escote, M. T.; Machado, MAC; Pizani, P. S.; Leite, E. R.; Sambrano, JR; Varela, José Arana [UNESP]; Longo, Elson [UNESP] (Elsevier B.V., 2004)
Li2TiSiO5 powders were synthesized by the polymeric precursor method. The calcination temperatures were progressively increased until the complete crystallization of the phase occurring at 870 degreesC. For the first time, a strong photoluminescence was measured at room temperature with a 488 nm excitation wavelength for the non-crystalline samples. This photoluminescence in disordered phases has been interpreted by means of high-level quantum mechanical calculations based on density functional theory. Two periodic models have been used to represent the crystalline and disordered powders. They allowed to calculate electronic properties consistent with experimental data and to explain the relations between photoluminescence and structural disorder. (C) 2004 Elsevier B.V. All rights reserved.